2019
DOI: 10.1109/access.2019.2904109
|View full text |Cite
|
Sign up to set email alerts
|

Battery-Less NFC Sensor for pH Monitoring

Abstract: In this paper, we present a low-cost battery-less color sensor based on Near Field Communication (NFC). This system consists of a color sensor connected to a low-power microcontroller connected to an NFC chip. The energy needed to power up the chipset is retrieved from the magnetic field generated by the reader, i.e., a commercial smartphone. The low cost of NFC chips affords the opportunity to manufacture low-cost tags with sensing capability. We have developed a mobile application to simultaneously present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Two relay antennas (Relay 1 and Relay 2) measuring 25×25 mm with 4 and 6 turns, respectively and three antenna sizes for the reader were analyzed. The size of the reader 1 and reader 2 antennas were similar to those integrated around cameras in smartphones, which is the typical position for mobiles with metallic cases [29]. The size of reader 3 antenna, on the other hand, was similar to that of antenna in the battery case for smartphones with plastic cases.…”
Section: Figure 12 Simulated and Measured Coupling Coefficients Betwmentioning
confidence: 80%
See 2 more Smart Citations
“…Two relay antennas (Relay 1 and Relay 2) measuring 25×25 mm with 4 and 6 turns, respectively and three antenna sizes for the reader were analyzed. The size of the reader 1 and reader 2 antennas were similar to those integrated around cameras in smartphones, which is the typical position for mobiles with metallic cases [29]. The size of reader 3 antenna, on the other hand, was similar to that of antenna in the battery case for smartphones with plastic cases.…”
Section: Figure 12 Simulated and Measured Coupling Coefficients Betwmentioning
confidence: 80%
“…The size of reader 3 antenna, on the other hand, was similar to that of antenna in the battery case for smartphones with plastic cases. In [29], the authors showed that the ferrite material used to isolate the coil from the battery or other metallic parts has a small influence on the coupling coefficient. The following simulations and measurements were therefore performed in the air.…”
Section: Figure 12 Simulated and Measured Coupling Coefficients Betwmentioning
confidence: 99%
See 1 more Smart Citation
“…Several companies, like TI-, AMS-, NXP- and ST-Microelectronics, commercially introduced very low-power NFC-integrated chips (ICs) to ensure enhanced data writing, reading and storing capabilities. Utmost importance has recently been given to energy harvesting and data communication from NFC, with a focus on the optimal ways to obtain some future directions [ 34 , 35 , 36 ]. This study designs a smart skincare device with a novel design approach that could harvest energy from an NFC-enabled smartphone and elaborates on the applications related to skincare.…”
Section: Introductionmentioning
confidence: 99%
“…Near-Field Communication (NFC) is a standard-based radio frequency (RF) channel communication architecture that can be embedded into several devices, such as mobiles cellphones, laptops, tablets, and NFC card readers [1]. Its main function allows to exchange data between devices in a proximity up to 10cm [2] using the 13.56 MHz frequency [3], [4], [5] with maximum data transfer rate of 424 kbit/s and low bandwidth [4], [6]. NFC technology was proposed over a decade, but it became popular when it was incorporated into payment systems, Internet of Things (IoT), information security, and Industry 4.0 [1], [3], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%